Characterization of a Dinuclear Copper(II) Complex and Its Fleeting Mixed‐Valent Copper(II)/Copper(III) Counterpart. Issue 4 (6th March 2017) - Kochem, Amélie; Gennarini, Federica; Yemloul, Mehdi; Orio, Maylis; Le Poul, Nicolas; Rivière, Eric; Giorgi, Michel; Faure, Bruno; Le Mest, Yves; Réglier, Marius; Simaan, A. Jalila
Abstract: The synthesis of a dinuclear copper(II) complex, supported by a 1, 3‐diamino‐2‐propanol‐based tetraamide ligand, is reported. Structural properties in the solid state and in solution, by means of XRD analysis and NMR spectroscopy, respectively, provide evidence of a highly flexible complex that can display several conformations, leading to the image of the wings of a butterfly. The complex was fully characterized and the redox properties were investigated. Room‐temperature spectro‐electrochemistry was used to monitor the formation of a metastable mono‐oxidized product that displayed an absorption band centered at λ =463 nm. EPR investigation of the low‐temperature, chemically generated, mono‐oxidized product reveals the presence of an intermediate described as a mixed‐valent Cu II Cu III species, which is a model of the possible highly oxidizing intermediate in particulate methane monooxygenase. Abstract : Fleeting species : A flexible dinuclear copper(II) complex based on a tetraamide ligand that resembles a butterfly flapping its wings is characterized, along with its one‐electron oxidized species, which consists of an unstable mixed‐valent copper(II)/copper(III) species (see figure).